Factors affecting the exposure, vulnerability and emergency medical service capacity for victims of road traffic incidents in Kampala Metropolitan Area: a Delphi study. Issue 1 (December 2016) - Balikuddembe, Joseph; Ardalan, Ali; Zavareh, Davoud; Nejati, Amir; Kasiima, Stephen
Abstract Background The Kampala Metropolitan Area (KMA) is the fastest developing region in Uganda. Over recent years, this has placed exponential demand on the road sector, which consequently has contributed to rapid growth in motorized vehicles which, predisposes the region to a high risk of road traffic incidents (RTIs). A number of concerted road safety and post-crash management measures to respond to RTIs in the KMA in particular and Uganda as a whole have been undertaken. However, there is a need to greatly improve the measures by better identifying the factors influencing the exposure, vulnerability and emergency medical service (EMS) capacity for RTI victims. The present study seeks to investigate and reveal these factors. Methods A Delphi technique employing a questionnaire and involving a multidisciplinary panel of experts was used in three rounds. Results The ten (10) most important factors affecting the exposure, vulnerability and EMS capacity for victims of RTIs in the KMA were identified. Socio-cultural, infrastructure and road safety aspects were the factors most identified as affecting the exposure and vulnerability. The absence of a national EMS policy and post-crash care system, as well as the fact that many victims lack health insurance, were noted to be the factors adversely affecting the EMS capacity. Conclusions There exists is a real need to substantially reduce the burden of RTIs in KMA, with ultimate goal of saving lives that are being lost needlessly and reducing the impact of injuries and trauma and the economic losses associated with it. This study offers insights into the causes of RTIs and the most appropriate ways of responding to them especially with the establishment and empowerment of predefined and structured EMS systems.